The Rise of the Image Banks – a Threat for the Advertising Photography? - Kotsev, Angel (Sledva : NBU Journal of Humanities and Arts, 2019)
The study presented in this article is part of the topic The Impact of Image Banks on the Advertising Photography in Bulgaria, which in turn is part of the doctoral thesis Trends in the Development of Bulgarian Advertising Photography in the Period 2000 – 2017. The purpose of the research is to explore the trends in the selection of an advertising image, i.e. when the preferred images are from image banks and when they are custom-made. The survey will present the number of photographs in Bulgarian advertisements taken from an image bank and the amount of custom made ones. Another issue considered is at what stages of the working advertising process stock images appear. What is also discussed is whether the stock image generating industry is detrimental to customized advertising photography and if it provides additional business opportunity for advertising photographic studios. Through analysis and in-depth interviews with art directors, custom commercial photographers and stock image photographers, the research will attempt to present and systemize specific trends in the working process of advertising agencies on the Bulgarian market and how this affects the advertising photography in Bulgaria. The term advertising photography will be used in the sense of custom photography created for a particular advertising project, while the term stock photography will be used to define a photograph created without a specific assignment and of general commercial nature.